Utilization of Polyethylene Terephthalate (PET) Plastic Waste as Material in AC-WC Mixture - Hafidz, Muhammad; Mayuni, Siti; Azwansyah, Heri (Jurnal Teknik Sipil, 2025)
Plastic waste is a global environmental issue that also poses significant challenges in Indonesia. As one solution, the utilisation of Polyethene Terephthalate (PET) waste as an additive in asphalt concrete wearing course (AC-WC) mixtures has been developed to enhance the mechanical performance of pavements while reducing environmental impact. This study aims to determine the Optimum Asphalt Content (OAC), analyse the performance of the asphalt mixture, and evaluate its Marshall characteristics. The research was conducted in two stages based on the 2018 Bina Marga specifications (revision 2): the first stage involved determining the OAC without PET (using asphalt content variations of 4,5%"“6,5%), while the second stage tested mixtures containing PET at varying proportions of 0%"“6% by asphalt weight. The results showed that the OAC was 5,7%. The addition of PET significantly increased Marshall stability by up to 40,85%, with the highest value of 1192,08 kg observed at 6% PET content. Increases were also noted in VFB and Marshall Quotient, whereas VIM, VMA, and Flow values tended to decrease. These findings suggest that PET waste has the potential to enhance the mechanical properties of asphalt mixtures while supporting sustainable plastic waste management initiatives.